2010
DOI: 10.1094/cchem-87-2-0141
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Compounds in Buckwheat (Fagopyrum esculentum Moench) Groats, Flour, Bran, and Husk

Abstract: Buckwheat is a pseudocereal with a strong characteristic aroma. Compounds responsible for the aroma of buckwheat groats were recently identified, but the distribution of aromatic compounds between different fractions of the buckwheat kernel (flour, bran, and husk) is not yet known. In this study, the composition of aromatic compounds in buckwheat seed fractions was investigated and compared to the composition of aromatic compounds in groats produced from the same batch of buckwheat seeds. Volatiles from each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 10 publications
1
27
0
1
Order By: Relevance
“…Aroma compounds in common buckwheat were indentified and quantified with gas chromatography‐mass spectrometry (GC‐MS) (Janeš and others 2009). There were great differences between the profiles of aromatic compounds in different milling fractions obtained from common buckwheat seeds (Janeš and others 2010). Janeš and Kreft (2008) reported that salicylaldehyde was a characteristic aroma component of common buckwheat groats.…”
Section: Introductionmentioning
confidence: 99%
“…Aroma compounds in common buckwheat were indentified and quantified with gas chromatography‐mass spectrometry (GC‐MS) (Janeš and others 2009). There were great differences between the profiles of aromatic compounds in different milling fractions obtained from common buckwheat seeds (Janeš and others 2010). Janeš and Kreft (2008) reported that salicylaldehyde was a characteristic aroma component of common buckwheat groats.…”
Section: Introductionmentioning
confidence: 99%
“…These were responsible for green/woody odor, suggesting that they make great contributions to the flavor of foxtail millet. (E)-2-Nonenal and (E,E)-2,4-decadienal, which are responsible for the frying odor and green odor, have been reported to be particularly important odorants in buckwheat, in which they showed OAVs of 242 and 4,523, respectively (Janeš et al 2010). (E,E)-2,4-Decadienal in XG, whose OAV was 0, should be noted.…”
Section: Resultsmentioning
confidence: 86%
“…These compounds play a critical role in foxtail millet flavor and are the characteristic aroma compounds of foxtail millet. (E)-2-Nonenal and (E,E)-2,4-decadienal, which are responsible for the frying odor and green odor, have been reported to be particularly important odorants in buckwheat, in which they showed OAVs of 242 and 4,523, respectively (Janeš et al 2010). As shown in Table II, aldehydes made up the largest group of odor-active volatiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these compounds, hexanal, 1-hexanol, nonanal, and 1-octen-3-ol have also been reported in poppy seeds and groats [38,39]. Hexanal is particularly abundant in both seeds.…”
Section: 3mentioning
confidence: 99%